Implementasi Model Mediasi Dalam Pengelolaan Konflik Siswa Di SMP Plus Darus Sholah Jember - Alpina Damayanti; Nathila F. Faqih; Mu'alimin Mu'alimin (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research discusses the role of mediation models in handling conflicts between students in the school environment. Conflict between students can affect their academic and social well-being, as well as the overall climate at school. The mediation model has been identified as a potential approach to resolve such conflicts in a constructive and inclusive manner. This research involves implementing a mediation model in a school as a conflict resolution strategy. This research aims to find out how the mediation model is implemented in managing student conflicts at SMP Plus Darus Sholah Jember. This research was conducted through a qualitative descriptive approach using interview instruments, documentation and literature study. The subjects of this research were the principal and students at SMP Plus Darus Sholah Jember. The results of the research show that conflicts between students that often occur are truancy, dating, violence and bullying. The results of the mediation services carried out by the school show that there is student awareness, an attitude of peace, and the re-establishment of harmonious relationships between students and parents. The mediation service provided by the school can be said to be effective, because all parties starting from students, teachers, homeroom teachers, guidance counselors, parents and school principals participate in conflict resolution.